2010
DOI: 10.1016/j.wneu.2010.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Intracranial Aneurysms After Successful Neck Clipping

Abstract: BACKGROUND: To report the authors' experience with recurrent aneurysms after primarily completely clipped cerebral aneurysms and discuss mechanisms of recurrence and recommended management. METHODS: Data were available for 1016 consecutive patients who underwent clipping of ruptured and unruptured aneurysms in a 15-year period from 1993-2007. RESULTS: Nine patients were treated for recurrent aneurysms after successful complete clipping of the initial aneurysms; six patients had initial surgery before 1992, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…221 A recent study reported a lower incidence of hemorrhage, with only 2 patients (0.2%) having SAH and a total of 9 patients (0.9%) having recurrent aneurysms among 1016 aneurysms clipped over a 15-year period; however, follow-up was not routinely performed in this series, and thus, the true incidence of recurrence is unclear. 222 Given the inclusion of both UIA and RIA, these results may not be generalizable to UIA alone. Although overall reported rates of recurrence appear to be very low, the limited available data suggest that recurrence rates may increase with incompletely clipped aneurysms and longer lengths of follow-up.…”
Section: Efficacy and Durabilitymentioning
confidence: 92%
“…221 A recent study reported a lower incidence of hemorrhage, with only 2 patients (0.2%) having SAH and a total of 9 patients (0.9%) having recurrent aneurysms among 1016 aneurysms clipped over a 15-year period; however, follow-up was not routinely performed in this series, and thus, the true incidence of recurrence is unclear. 222 Given the inclusion of both UIA and RIA, these results may not be generalizable to UIA alone. Although overall reported rates of recurrence appear to be very low, the limited available data suggest that recurrence rates may increase with incompletely clipped aneurysms and longer lengths of follow-up.…”
Section: Efficacy and Durabilitymentioning
confidence: 92%
“…This allows planning of follow-up intervals and retreatment and the prediction of rebleeding risks. 2,3,5,7,11,12 Because the goal of surgical aneurysm therapy is total and permanent occlusion of the aneurysm, partial occlusion has been seen as a failure due to the potential consequences of recurrent aneurysm hemorrhage. 3,11 Factors like the size and shape of the reperfused aneurysm, the relation of the open aneurysm part to the parent vessel, and the challenge of predicting the risk of rebleeding have been widely discussed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Aneurysm remnants are evaluated and followed up mostly by angiography. Multiple attempts have been made to categorize the great variety of different types of aneurysm remnants, 2,[5][6][7][8] but only a few articles have been published concerning the angiographic assessment details being used to delineate and quantify aneurysm remnants after aneurysm clipping. 2,4,9 All authors based the angiographic assessment on the criterion standard of the subjective occlusion rating (SOR).…”
mentioning
confidence: 99%
“…Case reports and series have found that even when aneurysms appear to be completely occluded after surgery, recurrence and rupture may occur later. The incidence of recurrent aneurysms after complete clipping was approximately 0.02% per year; aneurysms recurred after 13.3 years on average with 25 years the longest duration from initial clipping to recurrence [66] . Repeat craniotomy may be performed to prevent the rebleeding.…”
Section: Postoperative Image Evaluationmentioning
confidence: 96%